Electrification and appliance ownership over time: Evidence from rural India. (October 2019) - Richmond, Jennifer; Urpelainen, Johannes
Abstract: Rural electrification has the potential to transform rural lives and livelihoods by allowing households to use a variety of electric appliances. However, empirical evidence on how rural electrification translates into appliance ownership and usage remains understudied across contexts. Here we use data from the 2014–2015 ACCESS survey in six energy-poor states of India to understand the dynamics of appliance stock accumulation as a function of time since electrification. We find that, controlling for a number of variables, each additional year of electricity access leads to: 1) incrementally higher ownership rates of more power-intensive appliances, 2) increased likelihood of a higher total stock of appliances, and 3) increased probability of owning key appliances, especially TVs, fans, and pressure cookers. These results may help to explain why short-term impact evaluations sometimes find weak evidence for benefits of rural electrification; they also underscore the importance of realistic forecasts of energy demand growth over time after rural electrification. Highlights: Survey data analysis of electric appliance ownership in rural India. Appliance ownership grows slowly with time since household electrification. Subsequent benefits of household electrification accumulate slowly over time.